x+12=-(13)

Simple and best practice solution for x+12=-(13) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+12=-(13) equation:


Simplifying
x + 12 = -1(13)

Reorder the terms:
12 + x = -1(13)

Multiply -1 * 13
12 + x = -13

Solving
12 + x = -13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12' to each side of the equation.
12 + -12 + x = -13 + -12

Combine like terms: 12 + -12 = 0
0 + x = -13 + -12
x = -13 + -12

Combine like terms: -13 + -12 = -25
x = -25

Simplifying
x = -25

See similar equations:

| 50b+3c= | | 9+3(3x+5)=24+9x | | 50b+3= | | 60/p=4;15,16,17 | | 1/2x5/4 | | 2(14)-x+8=0 | | x/-7=(-5) | | -5x+13=-15 | | z+2=z | | 8b+10b+2+3b= | | s=6r^3(s/6r^3) | | -10+6x=3x-4 | | X/48=5/6 | | 7x+5=-5x | | 9(x+2)-7=2x+11 | | 0.25y=2/3-6 | | 1=-2x+16 | | 6.4*8.4=52.08 | | y=-2(1)+16 | | X^2+8y+2x-23=0 | | 0=-16t^2+128t+30 | | 8x-168=2x+562 | | 15+3(4-3x)=2x-6 | | 0.72a=14.25 | | X^2+42-32=0 | | 5-4j+j-1=-23 | | 3/5=8-y/10 | | M=3/8•4 | | 2x-[5(x+4)]= | | 2x+8=4x-11 | | 7(2m-3)=31 | | x^(-4/5)=0 |

Equations solver categories